Abnormalities in signaling pathways in diabetic nephropathy. Issue 1 (January 2010) - Brosius, Frank C; Khoury, Charbel C; Buller, Carolyn L; Chen, Sheldon
Diabetic nephropathy (DN) is characterized by a plethora of signaling abnormalities that together ultimately result in the clinical and pathologic hallmarks of DN, namely progressive albuminuria followed by a gradual decline in glomerular filtration rate leading to kidney failure, and accompanied by podocyte loss, progressive glomerular sclerosis and, ultimately, progressive tubulointerstitial fibrosis. Over the past few years, the general understanding of the abnormalities in signaling pathways that lead to DN has expanded considerably. In this review, some of the important pathways that appear to be involved in driving this process are discussed, with special emphasis on newer findings and insights. Newer concepts regarding signaling changes in bradykinin, mTOR, JAK/STAT, MCP-1, VEGF, endothelial nitric oxide synthase, activated protein C and other pathways are discussed.